Media consumption by preschool children: the risk of autism and developmental disorders - Kamp-Becker, Inge; Poustka, Luise (Deutsches Ärzteblatt, 2025)
Background: Autism spectrum disorder (ASD) is a persistent neurodevelopmental condition characterized by impaired social communication and the presence of restricted, repetitive patterns of behavior, typically manifesting in early childhood. The rising prevalence of ASD has been discussed in relation to increased media consumption. Methods: A selective literature search was conducted in the Medline database on the topics of media consumption and mental disorders, particularly autism, in preschool children. Seven systematic reviews and meta-analyses and 36 original studies were included in the analysis. Results: The findings across studies consistently demonstrated that media consumption in preschool children was associated with deficits in language and cognitive development (adjusted odds ratio [aOR] 1.67–2.28) and was a risk factor for the development of emotional, behavioral, and developmental disorders (aOR: 1.34–3.06). Symptoms consistent with ASD were also found to be associated with increased media consumption (OR 1.97, 95% confidence interval [1.30; 3.00]). However, these observed effects were consistently identified in the context of multiple other risk factors for mental health problems—such as low socioeconomic status,a family history of mental disorders, or parental stress—which mediated these effects, either directly or indirectly. Intervention studies showed that reducing media consumption, combined with an increase in constructive parent–child interactions, led to a reduction in symptom severity. Conclusion: In the context of additional risk factors,increased media consumption in young children is associated with atypical or delayed development. The extent of developmental disorders can be reduced through targeted support for parents. When risk factors are present, it is therefore essential to educate parents and implement preventive measures to promote the long-term healthy development of children.